Ultra Low Noise CMOS Image Sensors - Boukhayma, Assim (Springer Theses, Recognizing Outstanding Ph.D. Research, 2018)
This thesis provides a thorough noise analysis for conventional CIS readout chains, while also presenting and discussing a variety of noise reduction techniques that allow the read noise in standard processes to be optimized. Two physical implementations featuring sub-0.5-electron RMS are subsequently presented to verify the proposed noise reduction techniques and provide a full characterization of a VGA imager. Based on the verified noise calculation, the impact of the technology downscaling on the input-referred noise is also studied. Further, the thesis covers THz CMOS image sensors and presents an original design that achieves ultra-low-noise performance. Last but not least, it provides a comprehensive review of CMOS image sensors.